(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
This study evaluated the growth performance of broiler chickens fed diets containing varying levels of Pleurotus tuber-regium (PTR). A total of 120 broiler chicks were randomly assigned to four dietary treatments: T1 (control, no PTR), T2 (2.5% PTR), T3 (5.0% PTR), and T4 (7.5% PTR) in a completely randomized design for eight weeks. Each treatment had three replicates with 10 birds per replicate. Feed intake, weekly weight gain, and feed conversion ratio (FCR) were recorded, and data were analyzed using One-way analysis of variance (ANOVA) to determine the significant effects of the treatments on the response variables. Means were separated using Duncan’s new multiple range test. Significant differences (P<0.05) were observed in body weight, weight gain, feed intake, and FCR among the experimental diets. The control group (T1) recorded the highest body weight (3.66 kg) and weight gain (2.16 kg). Inclusion of 2.5% PTR (T2) did not significantly affect weight gain compared to the control, while higher inclusion levels (T3, T4) reduced feed intake at certain weeks. T1 and T2 had the lowest FCR, indicating better feed efficiency. The study concluded that dietary inclusion of tuber mushrooms up to 2.5% posed no adverse effects on growth performance. It is recommended that 2.5% PTR can be safely included in broiler diets to maintain growth without compromising feed efficiency. Higher levels may reduce feed intake and should be further investigated.